2004
DOI: 10.1159/000081918
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity among Isoniazid-Resistant Isolates of <i>Mycobacterium tuberculosis</i> from Rashid Hospital in Dubai, United Arab Emirates

Abstract: Objective: To perform molecular fingerprinting for strain relatedness among isoniazid-resistant Mycobacterium tuberculosis isolates recovered from tuberculosis (TB) patients in the United Arab Emirates (UAE). Materials and Methods: Thirty-two consecutive isoniazid-resistant M. tuberculosis strains isolated from TB patients (4 natives and 28 expatriates) at Rashid Hospital, Dubai, UAE were analyzed. The typing was carried out by touchdown double-repetitive-element PCR (DRE-PCR). The status of R463 or L463 polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This could be explained by the maintenance of the 30%~40% catalase-peroxidase activity in the INH resistant strain with the katG 315 Thr mutation [5,6] compared to other mutations related to drug resistance. Consequently, this allele was suspected as the cause of some earlier reported outbreaks [26-28] of INH resistant TB in specific areas and populations. Furthermore, the current study observed that in a cluster containing strains with different drug resistance profile and resistance conferring mutations, the INH resistance was caused by this mutation.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the maintenance of the 30%~40% catalase-peroxidase activity in the INH resistant strain with the katG 315 Thr mutation [5,6] compared to other mutations related to drug resistance. Consequently, this allele was suspected as the cause of some earlier reported outbreaks [26-28] of INH resistant TB in specific areas and populations. Furthermore, the current study observed that in a cluster containing strains with different drug resistance profile and resistance conferring mutations, the INH resistance was caused by this mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The expatriates mostly originate from poor/developing countries of south/southeast Asia (e.g., India, Pakistan, Afghanistan, Nepal, Bangladesh, Sri Lanka, and Philippines) and Africa (e.g., Ethiopia, Sudan and Nigeria) where many infectious diseases such as malaria, tuberculosis, taeniasis etc. are endemic [4,5,[14][15][16][17][18][19][20]. The number of malaria cases reported from the countries from which most of the expatriates working in GCC countries originate and the number of expatriates from these countries presently living in GCC countries are provided in Table 2.…”
Section: Epidemiology Of Malaria In the Middle East Region Countriesmentioning
confidence: 99%
“…As stated above, many countries in the Middle East Region, particularly GCC countries have a large expatriate population [14,[16][17][18][19][39][40][41][42]. Many expatriates originate from malaria endemic countries such as Sudan, Ethiopia and Nigeria in Africa and India, Pakistan, Afghanistan, Bangladesh and Philippines in Asia.…”
Section: Epidemiological Data From Countries Of Origin For Imported Mmentioning
confidence: 99%
“…In the GCC countries, expatriate workers from countries with a high prevalence of TB contribute to the occurrence of new cases and sustained TB transmission [2–5]. In Saudi Arabia, the TB incidence rate among expatriates doubles that for Saudi nationals and most non‐Saudi patients originate from countries with high TB endemicity [5,6].…”
Section: Tuberculosis (Tb)mentioning
confidence: 99%